2003
DOI: 10.4141/a02-067
|View full text |Cite
|
Sign up to set email alerts
|

Response of early weaned piglets to graded levels of dietary cobalamin

Abstract: House, J. D. and Fletcher, C. M. T. 2003. Response of early weaned piglets to graded levels of dietary cobalamin. Can. J. Anim. Sci. 83: 247-255. The water-soluble vitamin cobalamin plays a central role as a co-factor in key pathways of energy and protein metabolism. The dietary requirement of this vitamin for the young pig (5-10 kg) has been estimated at 17.5 µg kg -1 , but it is derived from estimates made over 40 yr ago. In light of changes in swine production, including the selection for high lean potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…Overall, during the whole experimental period, plasma vitamin B 12 concentrations in V1 (136.8 + 4.7 pM) and V2 (156.8 + 6.6 pM) pigs were approximately 35% and 54% higher, respectively, than for V0 (101.6 + 3.5 pM) (Figure 1). Such response of plasma vitamin B 12 to dietary cyanocobalamin is in line with results reported for post-weaning pigs by House and Fletcher (2003), where effects on plasma vitamin B 12 were observed between 0 and 35 mg/kg with no further significant increase beyond 35 and up to 140 mg/kg of dietary cyanocobalamin. However, the present results differ from recent observations in gilts (Simard et al 2007) showing that the concentration of cyanocobalamin, which maximised plasma vitamin B 12 , was estimated at 164 mg/kg.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, during the whole experimental period, plasma vitamin B 12 concentrations in V1 (136.8 + 4.7 pM) and V2 (156.8 + 6.6 pM) pigs were approximately 35% and 54% higher, respectively, than for V0 (101.6 + 3.5 pM) (Figure 1). Such response of plasma vitamin B 12 to dietary cyanocobalamin is in line with results reported for post-weaning pigs by House and Fletcher (2003), where effects on plasma vitamin B 12 were observed between 0 and 35 mg/kg with no further significant increase beyond 35 and up to 140 mg/kg of dietary cyanocobalamin. However, the present results differ from recent observations in gilts (Simard et al 2007) showing that the concentration of cyanocobalamin, which maximised plasma vitamin B 12 , was estimated at 164 mg/kg.…”
Section: Resultssupporting
confidence: 92%
“…The present increased importance of vitamin B 12 on homocysteine response during the finishing period might be in line with the previously mentioned discrepancy of plasma vitamin B 12 responses to dietary cyanocobalamin between piglets, growing-finishing pigs and gilts. In fact, the marginal plasma homocysteine response in V2 vs. V1 pigs during the growing period is consistent with the optimal dietary cyanocobalamin of 35 mg/kg reported by House and Fletcher (2003) for young piglets using plasma homocysteine as a criterion. In contrast, the homocysteine response of V2 over V1 pigs during the finishing period (i.e.…”
Section: Metabolic Measurementssupporting
confidence: 85%
“…Along with the liver content of this vitamin, pHcy appears therefore as a relevant and reliable indicator of B 12 status. This is in agreement with House and Fletcher (2003) who used pHcy as a criterion to determine B 12 requirement for post-weaned piglets.…”
Section: Piglet Metabolismsupporting
confidence: 86%
“…Research in early-weaned piglets has shown that current estimates of vitamin B 12 requirements are too low for this class of pig (House and Fletcher 2003), as evidenced by their increased plasma homocysteine concentrations and low plasma vitamin B 12 levels. In this previously cited study (Giguère et al 2005), the vitamin B 12 concentrations in meat increased as dietary B 12 increased.…”
Section: Water-soluble Vitaminsmentioning
confidence: 99%